The Vanuatu Psychiatry Mentorship Programme: supporting the development of a fledgling mental health service in the Pacific. (February 2020) - Obed, Jimmy; Bush, Allister; Stathis, Stephen; Hunter, Ernest
Objective: To describe the Vanuatu Psychiatry Mentorship Programme (VPMP) set up to support the sole mental health doctor and local nurses developing mental health service capacity in Vanuatu. Method: Following a request from Vanuatu, the VPMP was set up under the auspices of the Faculty of Child and Adolescent Psychiatry of the Royal Australian and New Zealand College of Psychiatrists (the College) with three components: regular online supervision, yearly onsite visits and advice over the Internet on an as-required basis. Results: Onsite visits undertaken by three VPMP psychiatrists provided opportunities for mentoring and teaching activities related to clinical psychiatry, community liaison, social and ethical considerations and mental health policy matters. Online supervision sessions were initially hampered by technology difficulties. Ad hoc advice over the Internet allowed more rapid responses in complex acute psychiatry cases. Conclusions: Structured mentoring programmes can play a role in supporting the development of mental health capacity in low-resourced Pacific nations. Such programmes are likely to be more useful for Pacific participants if they are flexible, ongoing, sustained by support from the College and reviewed regularly.